2012
DOI: 10.2320/matertrans.maw201218
|View full text |Cite
|
Sign up to set email alerts
|

<i>In-Situ</i> Evaluation of Detwinning Behavior in Extruded AZ31 Mg Alloy by AE

Abstract: Tension twinning readily occurs under compressive loading along extrusion direction because extruded AZ31 Mg plate has the texture with the basal planes parallel to the extrusion direction. Detwinning occurs in the twinned areas during tensile loading in the opposite direction. In this study, acoustic emission (AE) during the tensile test was investigated for the evaluation of detwinning behavior. Different AE features depending on the strain level were observed and detwinning behavior was divided into three s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
(14 reference statements)
0
4
1
Order By: Relevance
“…Partial detwinning is observed clearly at this strain level. In contrast to the detwinning induced by reverse loading, which left residual lenticular twins without twinning traces, as observed by Caceres et al [6] and Yasutomi and Enoki [21], the detwinning behaves very inhomogeneously under the present conditions and seems to initiate not from the tips but in the interiors of preexisting twins. Therefore, the residual twins observed in the present research are much more irregular; distinct twin boundary traces are observed after detwinning, as indicated by the white lines in the IPF map (figure 9(a)) and the contrast in the IQ map (figure 9(b)).…”
Section: Resultscontrasting
confidence: 45%
See 1 more Smart Citation
“…Partial detwinning is observed clearly at this strain level. In contrast to the detwinning induced by reverse loading, which left residual lenticular twins without twinning traces, as observed by Caceres et al [6] and Yasutomi and Enoki [21], the detwinning behaves very inhomogeneously under the present conditions and seems to initiate not from the tips but in the interiors of preexisting twins. Therefore, the residual twins observed in the present research are much more irregular; distinct twin boundary traces are observed after detwinning, as indicated by the white lines in the IPF map (figure 9(a)) and the contrast in the IQ map (figure 9(b)).…”
Section: Resultscontrasting
confidence: 45%
“…During the subsequent compression along the ED, there are two possible twinning variants for detwinning: reorientation of the c -axis forward by another 87° following (2) * (3), which is the same twinning variant that occurs during radial compression, and reorientation in the reverse direction to the original position following (2) * (1). Detwinning through the (2) * (1) route will give rise to a complete disappearance of the twin boundary or no twinning trace, like that during reverse loading [21, 25]. In contrast, detwinning through the (2) * (3) route actually proceeds through {10-12}-{10-12} re-twinning which will be accompanied by a transition of the twin boundaries (87°) into LABs with misorientation angles of about 6° (figure 8).…”
Section: Resultsmentioning
confidence: 99%
“…Observations of AE associated with de-twinning in a strongly textured commercial purity Mg were reported recently by Enoki and co-authors [43,44]. In this context, the specific features of AE response in the CTC loading path to the first reversal from compression to tension are of interest.…”
Section: Signatures Of De-twinning In the Ae Signalmentioning
confidence: 83%
“…Twinning provides a high dislocation slip by producing more barriers between grains [22]. Moreover, Koike et al [23], Barnett [24,25] and Yasutomi and Enoki [26] argued that twinning formation results in extruded materials from the extrusion process. Figure 8 shows the effect of strain rate on elongations of extruded AZ31 and AZ61 magnesium alloys.…”
Section: Resultsmentioning
confidence: 99%